A case of Non-compaction of Left Ventricle Coexistent with Juvenile Nephronophthisis. Is this Another Presentation of Ciliopathy? - Momtaz, Hossein Emad; Tanasan, Asadolah; Afkhami, Mojdeh (Journal of Pediatric Nephrology, 2014)
Nephronophthisis is a chronic tubulo-interstitial nephritis which can progress to end-stage renal disease. Juvenile nephronophthisis is the most common type of nephronophthisis, which accounts for 5-10% of the cases of pediatric end stage renal diseases. Left ventricular non-compaction (LVNC), a rare form of cardiomyopathy, is the result of intrauterine arrest of compaction of the endomyocardial morphogenesis. Clinical manifestations of LVNC range from asymptomatic child to a progressive deterioration in the cardiac function, congestive heart failure, arrhythmias, systemic thromboembolism and sudden cardiac death. This report presents a case of juvenile nephronophthisis with LVNC. A 15-year-old boy was referred to our nephrology outpatient clinic with a 6-month history of non-specific complaints such as lethargy, anorexia, polydipsia, polyuria, and pallor. Abdominal sonography showed a generalized increase in the parenchymal echo of kidneys. Renal biopsy was performed for him which showed nephronophthisis. Echocardiography was done and revealed LVNC. He was discharged with training for careful follow-up. Our reported case had nephronophthisis and LVNC. To the best of our knowledge, there is no report of this combination in the literature. This suggests that LVNC may be another presentation of cilia involvement. The clinical coexistence of LVNC and nephronophthisis could guide us to better localize and discover the underlying genetic mutations and the role of ciliopathies in various human diseases; Therefore, further research with a special focus on potential common derangement of cilia and protein products in these diseases is recommended. Keywords: Juvenile nephronophthisis; Isolated Noncompaction of the Ventricular Myocardium; Ciliary Motility Disorders